2021
DOI: 10.3354/ame01959
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the planktonic to sessile transition in a marine biofilm-forming Pseudoalteromonas isolate using comparative proteomic analysis

Abstract: Bacterial biofilms play an important role in marine biofouling. The formation of a biofilm starts when marine bacterial cells transition from a planktonic to an attached state. However, the molecular mechanisms involved in this transition are poorly understood. Here, 51 strains of marine bacteria were isolated from natural biofilms growing on submerged artificial surfaces (glass slides, epoxy panels, and bridge pillars) and evaluated for their biofilm-forming capacity. Eleven strains formed relatively strong b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In bacterial cells, this transition stage often involves a transcriptional reorganization that yields phenotypic and metabolic alterations. For instance, bacteria often lose their flagella and produce extracellular polysaccharides as stress responses, contributing to their persistence in favorable niches (Jefferson, 2004; Wu et al, 2021). Analogous behaviors have been observed in microalgae biofilms (Schnurr and Allen (2015) and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…In bacterial cells, this transition stage often involves a transcriptional reorganization that yields phenotypic and metabolic alterations. For instance, bacteria often lose their flagella and produce extracellular polysaccharides as stress responses, contributing to their persistence in favorable niches (Jefferson, 2004; Wu et al, 2021). Analogous behaviors have been observed in microalgae biofilms (Schnurr and Allen (2015) and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation, using scanning electron microscopy, demonstrated that the nonsynonymous mutations in galU had likely resulted in lipopolysaccharide overproduction that may have facilitated attachment to sediment (Fig. 2H) [42][43][44] . Thus, the NMDS analysis uncovered evidence that specific variants of both organisms had likely led to niche differentiation of the SynCom ecotypes across the planktonic and attached phases.…”
Section: Heterogeneity Of Population Structure and Genetic Variabilit...mentioning
confidence: 99%
“…Several of these bacteria exhibit unique capabilities that may contribute to their persistence over the 30-day cultivation period. This adaptability could potentially be attributed to factors such as metabolic versatility and biofilm formation, which are known to facilitate their successful adaptation in extended cultivation environments (Riyaz et al, 2019;Wu et al, 2021). While these hypotheses are founded on existing research, they should be viewed as plausible explanations rather than definitive confirmations solely dependent on the presence of specific bacterial species.…”
Section: Comparison Of Bacterial Profiles On Day 1 and 30 Of Cultivationmentioning
confidence: 99%